What's the Good of the Market? An Essay on Michael Sandel's What Money Can't Buy - Besley, Timothy (Journal of Economic Literature, 2013)
This essay will discuss the criticisms of the economic approach to markets offered by Michael Sandel's What Money Can't Buy. After reviewing the main arguments, the essay looks at these from three main angles. First, it relates them to different traditions of thinking about markets and their achievements that have been developed by economists. Second, it discusses the idea that markets can change values as argued by Sandel in light of recent related literature in economics. Third, it discusses some of the literature on alternatives to using the market to allocate resources and the pros and cons of these. (JEL A11, A13, D40, D63, P10)